Ruqyah Menggunakan Ayat-Ayat Al-Qur’an: Analisis Metode Dan Praktik Ruqyah di Desa Cikurubuk - Muhammad Nasyiruddin Akmal (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to analyze the method and practice of ruqyah in Cikurubuk Village. The research method used is descriptive qualitative, which comes from observations and interviews in the village with related research. This study found that the practice of ruqyah that occurs in Cikurubuk Village uses verses of the Qur'an, the verses commonly used are Al-Baqarah verse 135, Ali 'Imran verses 18-19, Al-Baqarah verse 33, An-Nisa verse 45 and Al-Hasr verses 21-24 as well as Al-An'am verse 95 whose method of practice is to recite the verse to water.